GANGGUAN TIDUR DAN TENSION TYPE HEADACHE DI POLIKLINIK SARAF RSUD DR. M. HAULUSSY AMBON - Krisyel Rugebregt; Bertha J. Que; Paringotan Y. Silalahi (Fakultas Kedokteran Universitas Pattimura, 2019)
Tension type headache (TTH) is one type of primary headache that is often experienced by people nowsday that occurs due to muscle tension on the head and neck area. There are several trigger factor of TTH. One of them is sleep disorder. This study aims to determine the correlation between sleep disorder and TTH in patients of the neurological clinic of RSUD dr. M. Haulussy. This research is a correlative analytic research with cross sectional approach through primary data collection. Subjects in this study were 69 primary headache patients who were outpatient in neurology clinic of RSUD Dr. M. Haulussy uses consecutive sampling techniques. The TTH patient was obtained from a diagnosis of neurologist and sleep disorders data obtained from the questionnaire. The results showed a significant correlation (p <0.001) between sleep disorder and TTH in neurology clinic of RSUD dr. M. Haulussy Ambon with moderate correlation strength (r = 0.418).